Literature Review: Occupational Safety and Health Risk Factors of Healthcare Workers during COVID-19 Pandemic - Prima Ardiansah Surya; Marsheila Harvy Mustikaningtyas; Sacharissa Zerlina Tsarwah Thirafi; Afika Danedea Pramitha; Laksita Taffara Mahdy; Gery Morales Munthe; Adivia Cheries Dwiantoro; Budiono Budiono (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: The pandemic of COVID-19 has major effects, particularly on hospitals and health workers. At the beginning of March, more than 3,300 health workers have beencontracted with COVID-19 as reported by China's National Health Commission. Twenty percent of healthcare workers in Italy have also also infected and some died. To minimize the risk of transmission to health workers, knowledge of the risk factors that influence the transmission is needed. Thus, this study aims to determine risk factors related to occupational safety and health for healthcare workers during the COVID-19 pandemic. Methods: The literature was searched on Pubmed, Google Scholar, WHO, and the Ministry of Health instruments were implemented. 8 relevant studies were reviewed. Results: According to the analysis results of several studies, the use of PPE that is less consistent and not suitable with the risk of exposure will increase the risk of infection. The risk of infection is also increased by poor hand hygiene. According to the Kaplan-Meier curve, the working duration of ≥ 15 hours will increase the risk of infection. The risk of infection also exists for health workers who carry out risky procedures that generate airborne particles such as resuscitation, as well as environmental factors such as negative pressure rooms and traffic control bundling. Conclusion: Risk factors related to occupational health and safety during this COVID-19 pandemic for healthcare staff are: compliance with the use of PPE, hand hygiene, working hours duration, risky procedures, and environmental factors.Keywords: healthcare workers, occupational safety, COVID-19, personal protective equipment